2018
DOI: 10.1515/tlr-2018-2003
|View full text |Cite
|
Sign up to set email alerts
|

Split noun phrase topicalization in Eshkevarat Gilaki

Abstract: Split noun phrase topicalizationhas been the subject of intense studies across languages in the syntactic literature of the last few decades. One of the key questions raised for these constructions is whether they involve syntactic movement or base-generation. This paper explores this phenomenon in two understudied Iranian languages, Gilaki (Northwestern Iranian, Caspien) and Persian. In particular, we explore splits in two contexts, possessive constructions and numeral constructions. We develop diagnostics fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 19 publications
0
8
0
Order By: Relevance
“…The distinctive properties of both types of REZ are summarized in Table 4. It is important to note that the REZ with a dual nature is not peculiar to Balochi, but a similar distinction is also observed in other Caspian languages like Gilaki, in which two types of REZ are diagnosed with distinctive phonological and syntactic properties, (Kahnemuyipour et al 2020; see also chapter 5, this volume for the Gilaki facts, as well as chapter 9, 10 and 11 for a similar distinction in Sangesari, Taleshi and Tati).…”
Section: Ellipsismentioning
confidence: 61%
“…The distinctive properties of both types of REZ are summarized in Table 4. It is important to note that the REZ with a dual nature is not peculiar to Balochi, but a similar distinction is also observed in other Caspian languages like Gilaki, in which two types of REZ are diagnosed with distinctive phonological and syntactic properties, (Kahnemuyipour et al 2020; see also chapter 5, this volume for the Gilaki facts, as well as chapter 9, 10 and 11 for a similar distinction in Sangesari, Taleshi and Tati).…”
Section: Ellipsismentioning
confidence: 61%
“…Aside from these differences, Sangesari shares one core similarity with Caspian languages: Reverse Ezafe with attributive adjectives has a different form from the Reverse Ezafe used with possessors and adpositions, with different properties. This indicates that Reverse Ezafe is not a single phenomenon in all of these languages (see Kahnemuyipour et al 2020, to appear for discussion).…”
Section: Discussionmentioning
confidence: 97%
“…In general, Balochi is a Reverse Ezafe language, where the nominal modifiers and complements precede the head noun. Gündoğdu shows that the Reverse Ezafe that appears in the context of possessive and adpositional phrases has a different form and distinct properties from the one used between attributive adjectives and nouns (along the lines of Kahnemuyipour et al 2020 for Caspian languages). 4 It is further shown that the Reverse Ezafe used in the context of attributive adjectives is different from the one used with attributive nouns.…”
Section: This Volumementioning
confidence: 99%
“…The noun phrase in Sangesari is head-final, so the nominal linker used in this language is characterized as Reverse Ezafe. The authors show that the Reverse Ezafe used in possessive and adpositional contexts are realized as -i and that they do not pattern like the Reverse Ezafe used with attributive adjectives, which is realized as -a (see Kahnemuyipour et al 2020, to appear for discussion). The adpositions in Sangesari are mostly postpositions, and the authors show that Sangesari postpositions can be either nominal or true, with only nominal postpositions allowing Reverse Ezafe.…”
Section: This Volumementioning
confidence: 99%
See 1 more Smart Citation